DINAMIKA PENGELOLAAN SUMUR MINYAK TRADISIONAL DI RANTO PEUREULAK ACEH TIMUR - Rangkuty, Rakhmadsyah Putra; Ketaren, Amiruddin; Hidayat, Hidayat; Hidayat, Bimby; MR, M. Husen (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
This study was motivated by the existence of illegal oil drilling activities that have been going on for a long time and pose a high risk to the safety of workers, even local residents. Even though oil well fires often occur and victims suffer from burns and even death, this activity still continues. This research uses a qualitative approach, with a case study type of research based on observation, interview and documentation data. Meanwhile, technical analysis is carried out through Narrative Analysis. The research results show that the phenomenon of drilling old oil wells in Buket Pala Village has been carried out for decades. Mining workers have been able to utilize available resources so that they have more economic value. The old oil well has become the lifeblood of the village community. It is good for the mining community as well as for residents who receive an abundance of oil proceeds from "oil melting" activities. Apart from that, the existence of mining old oil wells also poses dangerous risks such as work accidents, fires, explosions and even fatalities. Apart from that, pollution and environmental damage will also occur. The situation was made worse because the activity did not meet standard operational procedures or technical requirements for the mining process. Therefore, in the future, efforts will be made to manage old oil wells by village/regional companies, namely BUMD/BUMG and Village Unit Cooperatives (KUD). This is intended to achieve the aim of improving the welfare of the community evenly around the location as well as to regulate the business of extracting oil from old wells, so that the management of existing old oil wells will no longer occur illegal drilling and increase village income.